ФІЛ ОСОФІЯ ЄВРОІНТЕГР АЦІЇ У РОЗВИТКУ СУЧАСНОЇ ОСВІТ И УКРАЇНИ: ПР ОБЛЕМ И ТА ПЕР СПЕ КТИВИ - Ovsyankina, L (Continuing Professional Education: Theory and Practice, 2019)
Modern progress of higher education of Ukraine trends and the basic requirements to highquality preparation of specialists are considered in the article. The strategic tasks of higher education, directed on the increase of intellectual, creative and moral level of development of future professionals, are analysed.